The advancement of Ethiopia's salt iodization programme-The success story of the central iodized facilities - Rizwan Yusufali; Denise Frohmann; Tesfaye Chuko; Arnaud Laillou (Wiley, 2024)
Abstract The objective of this article is to characterize the value of centralized iodization facilities (CIFs) to advance Ethiopia's salt iodization programme and its impact on the population iodine status. The analysis is based on a review of publications relating to salt iodization and iodine deficiency control efforts in Ethiopia. The country has made remarkable progress in improving iodized salt coverage, leading to improved iodine intake across its population that would otherwise be at high risk of iodine deficiency disorders. Establishment of central processing facilities, more frequent monitoring and generation of data and encouraging private sector investment have been instrumental in this achievement. Ethiopia has thus achieved and sustained greater than 89% HH iodized salt coverage from its lowest point of 15% coverage and subsequently improved iodine intake across its population. Iodine intake sufficiency in a population is assessed by median urinary iodine concentration (MUIC). The lessons learned and the experience with CIFs have applicability in several other countries where fragmented salt production continues to create barriers to achieve higher iodized salt coverage.